Environmental software systems. frameworks of eEnvironment 9th IFIP WG 5.11 international symposium, ISESS 2011, Brno, Czech Republic, June 27-29, 2011. proceedings - International symposium on environmental software systems 2011 Brno, Czech Republic); Hrebicek, Jiri.; Schimak, G. (Gerald).; Denzer, R. (Ralf).; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 9th IFIP WG 5.11 International Symposium on Environmental Software Systems, ISESS 2011, held in Brno, Czech Republic, in June 2011. The 68 revised full papers presented together with four invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections:eEnvironment and cross-border services in digital agenda for Europe; environmental information systems and services - infrastructures and platforms; semantics and environment; information tools for global environmental assessment; climate services and environmental tools for urban planning and climate change - applications and services.
Electronic reproduction.
Keywords: Environmental sciences -- Data processing -- Congresses; Ubiquitous computing -- Congresses; Sensor networks -- Congresses; Cloud computing -- Congresses; Electronic books